Big Data Analytics for the Integration of Electric Vehicles in Green Smart Cities (International Journal of Food and Nutritional Sciences, 2022)
The enormous information issue is characterized by the monstrous amount of information delivered by contraptions, vehicles, structures, the power framework, and numerous other associated objects, as well as speeding up. Brilliant framework and electric vehicles, among numerous different areas associated with the Internet of Things, face this issue as the two makers and purchasers (i.e., prosumers) of enormous information. Electric vehicles may significantly help brilliant urban communities in becoming greener by diminishing transportation area emanations, and they can assume a significant part in green shrewd urban communities. Here, we'll take a gander at a portion of the information investigation strategies that have been used to manage enormous information from brilliant frameworks and electric vehicles. Electric vehicles produce information from different sources, including sensors and excursion records. When this monstrous measure of information has been investigated utilizing enormous information procedures, it very well may be utilized to foster arrangements for siting charging stations, creating brilliant charging calculations, settling energy effectiveness issues, evaluating the limit of force dissemination frameworks to deal with extra charging loads, and deciding the market an incentive for the administrations given by electric vehicles (i.e., vehicles). This paper offers an exhaustive outline of the information investigation climate around the reconciliation of electric vehicles into green brilliant urban communities. It fills in as a guide for future information examination prerequisites and answers for the reconciliation of electric vehicles into brilliant urban communities.